The CEO's emotional bias and the delegation of decision-making rights. Issue 5 (10th June 2020) - Souissi, Yasmine; Salhi, Bassem; Jarboui, Anis
Abstract : Purpose: The purpose of this paper is to document the relation between the bank's regional CEO's emotional bias (optimism and loss aversion) and the delegation of decision rights to the account manager. Design/methodology/approach: The partial least squares (PLS) method is applied to investigate the degree to which bank's regional CEO delegate decisions and the circumstances that drive variation in delegation. Findings: The results show that delegation does not appear to be monolithic; instead, the results show that delegation varies with the personal characteristics of the bank's regional CEO. Practical implications: Banks are invited to take into account the effect of the emotional biases of the directors on the delegation of its power. Originality/value: The authors put forward an original effort that is intended to discuss in particular the effect of psychological biases on the decentralization of the decision-making rights.